TiO2–Graphitic Carbon Nitride-based Nanocomposites for the Degradation of Emerging Pollutants - Devagi, Kanakaraju; Ying Chin, Lim (The Royal Society of Chemistry (RSC), 2024)
TiO2-based nanocomposites have been extensively explored as potential materials for the degradation of various emerging pollutants such as pharmaceuticals, dyes, and pesticides. The material’s photocatalytic performances have been continually improved via the inclusion of semiconductor(s), cocatalysts, and doping. Graphitic carbon nitride (gC3N4) is regarded as a good visible light photocatalyst for the modification of TiO2 and its nanocomposites. Binary TiO2–gC3N4 and TiO2–gC3N4-based nanostructures have been synthesized in related studies via various synthesis methods and routes such as sol–gel, hydrothermal, solvothermal and microwave methods to produce highly visible-light responsive materials with enhanced charge separation and photocatalytic activity. The type of precursors and calcination conditions also greatly influence the material’s surface, optical morphology, and finally their photocatalytic activities. Both binary TiO2–gC3N4 and TiO2–gC3N4-based nanostructures exhibit great potential in removing emerging pollutants and can be further exploited in achieving enhanced photocatalytic performance.